Pemasaran Syariah dalam Upaya Optimalisasi Peran Lembaga Amil Zakat di Indonesia - Siti Kalimah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2019)
Abstract The purpose of this research is to know the role of Sharia marketing strategy in supporting the role of Lembaga Amil Zakat especially in the optimization of fundraising Zakat, Infaq, charity, and Waqaf (ZISWAF) from the community. The research uses a library research approach. Indonesia has a vast number of people and the majority are Muslims. Nevertheless, there are still some communities that are still under the poverty line which is about 9.66% of the total number of Indonesian people in 2018 as many as 265 million people. The role of Lembaga Amil Zakat (LAZ) in optimizing the collection and management of funds (ZISWAF) is expected to suppress the poverty rate. But in practice still, lack of knowledge and public awareness in fulfilling its obligation to pay zakat. Most of the community considers that zakat must be paid annually is Zakat Fitrah, while Zakat mal (treasure) is not mandatory. Therefore the necessity of proper marketing strategy and by following the mission-vision of the Institute of Amil Zakat (LAZ) should be applied. The institution of Amil Zakat can conduct sharia marketing strategy, namely implementing the process segmenting, targeting, positioning in their marketing and framed in a product that is suitable Islamic sharia. The introduction or socialization of the products of the Amil Zakat institution must be on target and can reach all walks of life quickly. Therefore, the use of technology is also needed to accelerate the socialization, expanding the reach, and supporting the concept of transparency so that the belief in the Society of Amil Zakat can increase.